COMPARISON OF NUMERICAL MODELS OF PORTS OF A STRIPLINE - Chaber, Bartosz; Starzyński, Jacek (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
The aim of the article is to describe different ways to model ports of structures like striplines or antennas. It also shows a practical realization of the models described, prepared with the use of COMSOL suite. Both, strong and weak points have been analyzed for each of the five versions, focusing on the factors as: complexity of the definition, time complexity and potential possibilities. In order to compare the accuracy each of the models had been used to calculate reflection coefficient, which in turn was compared to the data obtained from the measurements of the real stripline.